2011
DOI: 10.1016/j.jcta.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Substitution-closed pattern classes

Abstract: The substitution closure of a pattern class is the class of all permutations obtained by repeated substitution. The principal pattern classes (those defined by a single restriction) whose substitution closure can be defined by a finite number of restrictions are classified by listing them as a set of explicit families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The simple permutations form the elemental building blocks upon which all other permutations are constructed by means of the substitution decomposition. 3 Analogues of this decomposition exist for every relational structure, and it has frequently arisen in a wide variety of perspectives, ranging from game theory to combinatorial optimization -for references see Möhring [35] or Möhring and Radermacher [36]. Its first appearance seems to be in a 1953 talk by Fraïssé (though only the abstract of this talk [25] survives).…”
Section: Substitution Decompositionmentioning
confidence: 99%
“…The simple permutations form the elemental building blocks upon which all other permutations are constructed by means of the substitution decomposition. 3 Analogues of this decomposition exist for every relational structure, and it has frequently arisen in a wide variety of perspectives, ranging from game theory to combinatorial optimization -for references see Möhring [35] or Möhring and Radermacher [36]. Its first appearance seems to be in a 1953 talk by Fraïssé (though only the abstract of this talk [25] survives).…”
Section: Substitution Decompositionmentioning
confidence: 99%
“…leftInflationleftSequence4.ptof4.ptsumleftSum4.ptclosureleftSequence4.ptof4.ptskewleftSkew4.ptclosureleftof4.pt25314leftindecomposablesleftgrowth4.ptrateleftindecomposablesleftgrowth4.ptrateleft256314left1,1,3,6,4,1left2.44874left1,1,3,4,3,1left2.36772left265314left1,1,3,5,4,1left2.41421left1,1,3,4,3,1left2.36772left263415left1,1,3,6,3,1left2.43245left1,1,3,4,3,1left2.36772left264315left1,1,3,4,3,1left2.36772left1,1,3,6,3,1left2.43245 Next, we show that the simple permutations of G2.36 are contained in Av(321)Av(123){25314,41352}. For this, we use a result of Atkinson, Ruškuc, and Smith . They showed that the substitution closure of a principally based class is typically infinitely based.…”
Section: Gridding Intermediate Classesmentioning
confidence: 99%
“…We may then choose an element x 2 ∈ X to be minimal such that x 1 , x 2 begins a bad sequence. Proceeding by induction 17 , if we assume that x 1 , x 2 , . .…”
Section: Proposition 52 (Nash-williams [79 Proof Of Lemma 2]) a Well-...mentioning
confidence: 99%
“…20 See Brignall and Vatter [30] for a proof of Schmerl and Trotter's theorem in the special case of permutations. 21 However, in practice it can be difficult to establish precisely what the members of the basis are, and there are frequently infinitely many of them-see Atkinson, Ruškuc, and Smith [17] for one such example.…”
Section: Proposition 710 (Albert and Atkinson [1]) The Basis Of The S...mentioning
confidence: 99%